Women: Transforming food systems for empowerment and equity - Malapit, Hazel J.; Meinzen-Dick, Ruth S.; Quisumbing, Agnes R.; Zseleczky, Laura (International Food Policy Research Institute, 2020)
Ensuring that women’s contributions to food systems are recognized—by their families, communities, policymakers, and society more broadly—and that women can make strategic choices about their involvement in food systems has benefits for all of society. KEY FINDINGS - Women are actively involved in food systems in many roles, but their contributions are often not formally recognized, and they face obstacles to engaging on equitable and fair terms. - Together with changing diets, transformation of food systems toward more efficient and sustainable pro-duction processes and longer value chains offers new opportunities and challenges for women’s participation. - Transforming food systems for inclusion means not just ensuring women’s participation and access to benefits but also their empowerment to make strategic life choices. - Entrepreneurship is often touted as a key to empowering women, but evidence indicates that it may not empower women if limited to small, household-based enterprises.